Functionally graded membranes from nanoporous covalent organic frameworks for highly selective water permeation. Issue 2 (13th December 2017) - Yang, Hao; Wu, Hong; Yao, Zhaoquan; Shi, Benbing; Xu, Ziang; Cheng, Xuanxuan; Pan, Fusheng; Liu, Guanhua; Jiang, Zhongyi; Cao, Xingzhong
Abstract : Functionally graded membranes with finely tuned COF gradients were fabricated for highly selective water permeation. Abstract : Natural materials are often arranged in intricate gradient architectures to implement specific functionalities. Implanting such an exquisite prototype into synthetic membranes remains a grand challenge in real-world applications. In this study, functionally graded membranes are fabricated through a surface segregation method using 2D nanoporous COF TpHZ and poly(ether sulfone) as composite building blocks. During the membrane formation, the COF nanosheets can spontaneously migrate from the membrane bulk to the membrane surface to form a gradient distribution, which can be varied by manipulating the COF addition content and phase inversion temperature. The highest COF content on the membrane surface can be up to 50.90 vol%. Due to the formation of a graded structure, the membranes are endowed with remarkably increased hydrophilicity and free volume characteristics. Accordingly, the optimized membrane exhibits a permeation flux of 2.48 kg m −2 h −1 and a high separation factor of 1430, and remains robust during a stability test for 320 h, and is one of the most efficient mixed matrix membranes for water/ethanol separation. The separation factor is two orders of magnitude more than that of existing commercial membranes. The concept of functionally graded membranes can be applicable to the development of a broad range of high-performance materials.